Analysis of Consumer Preferences Toward Frozen Chicken Nugget Products in Surabaya - Tri Redyta Febryanti; Ulya Sarofa; Yushinta Aristina Sanjaya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Frozen chicken nuggets are processed ground chicken with binding agents and seasonings, coated with breadcrumbs, heated, packaged, and frozen to maintain quality. Increasingly fierce competition between brands requires manufacturers to produce products that meet consumer needs. This study aims to analyze consumer preferences for frozen chicken nugget product attributes using Conjoint Analysis and Multiple Linear Regression. The results show that the attributes most influential on consumer preferences are flavor variants (28.46%), followed by package size (27.92%), price (27.12%), and crumb texture (16.51%), with the highest preference for the original variant, price <Rp20,000, packaging 100–250 grams, and bread crumbs coating. Regression analysis shows that brand, testimonials, availability, packaging design, product image (USP), and advertising have a significant positive effect on purchasing decisions, whereas labels do not. Simultaneously, all variables had a significant effect with a model contribution of 54.4%. The implications of this study indicate that the marketing strategy for frozen chicken nuggets in Surabaya should focus on increasing product availability, strengthening the brand image, and leveraging advertising and testimonials as promotional media. Contribution to Sustainable Development GoalsSDG 9 (Industry, Innovation, and Infrastructure)SDG 12 (Responsible Consumption and Production)SDG 8 (Decent Work and Economic Growth).